2012
DOI: 10.1007/s10266-012-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socio-demographic, socioeconomic, and water variables on dental fluorosis in adolescents growing up during the implementation of a fluoridated domestic salt program

Abstract: The objective of this study is to determine the impact of socio-demographic, socioeconomic, and other risk indicators on dental fluorosis (DF) among Mexican adolescents. A cross-sectional study was carried out in 1,538 adolescents 12 and 15 years of age in semi-rural communities located at high altitude (>2,000 m) and with high concentration of fluoride in water (1.38-3.07 ppm) in Hidalgo, Mexico. DF was determined by means of Dean's Index and all teeth were examined. Remaining variables were collected using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…Pontigo-Loyola et al . [22] also reported similar results showing that children aged 12 years had greater chance to have fluorosis compared to those aged 15 years. The epidemiology system for oral diseases (SIVEPAB)[23] in 2010 also proposed an increase in DF prevalence, especially in the younger age groups (under 25 years).…”
Section: Discussionmentioning
confidence: 65%
“…Pontigo-Loyola et al . [22] also reported similar results showing that children aged 12 years had greater chance to have fluorosis compared to those aged 15 years. The epidemiology system for oral diseases (SIVEPAB)[23] in 2010 also proposed an increase in DF prevalence, especially in the younger age groups (under 25 years).…”
Section: Discussionmentioning
confidence: 65%
“…REV BRAS EPIDEMIOL JUL-SEP 2015; 18(3): 568-577 conducted in Brazil and Latin America have shown an association between higher socioeconomic status and lower prevalence of fluorosis 9,10 , others have reported no association 3,[11][12][13] . Some studies have also reported association between better socioeconomic status and higher incidence of fluorosis [14][15][16] .…”
Section: Palavras-chavementioning
confidence: 99%
“…For example, it is well-established in the literature that the consumption of tap water with fluoride levels above 1.5 mg/L increases the likelihood of suffering more severe dental fluorosis [28]. This relationship has been found in studies in different states of Mexico (see [50][51][52][53]) and around the world (see [54][55][56]). Therefore, it is essential to provide information to affected households about the increased risk of developing dental fluorosis associated with tap-water consumption.…”
Section: Discussionmentioning
confidence: 92%